PROJETO DE UM SISTEMA DE CONTROLE DO CONSUMO DE COMBUSTIVEL DE UM VEÍCULO DE COMPETIÇÃO BAJA - BONFADA, ANDERSON R.; VADIERO, ANTONIO C.; ERHARDT, DAIANE M.; KAFKA, DAVID; ABENTROTH, FERNANDO H.; GILAPA, GENARO M. M.; BARBIERI, JOAO R. P.; STAMM, JOÃO G.; CARPES, JONATAS V.; HEIMBURG, JULIO C. V.; DANETTE, LUCAS I.; BATAGLIN, MARCELO; et al. (Salão do Conhecimento, 2013)
Resumo